KEPERCAYAAN PEMBELI TERHADAP PERUSAHAAN PEMASOK DALAM HUBUNGANNYA DENGAN ANTISIPASI PEMBELIAN DIWAKTU YANG AKAN DATANG - sri Vandayuli Riorini (Media Riset Bisnis & Manajemen, 2003)
The appropriate strategy of buying raw malerials is the key success of business operation in every company, because the suppliers are responsible in delermining and delivering a high quality product which can satisfy the customer's needs and wants. The purpose of this re- search is to investigate the relationship between reputation and supplier's or seller's size to the buyer trust, and relationship between buyer's trust and anticipated future interaction. For analyzing data, the study uses Structural Equation Model, statistical technique which enables testing of buitd between one or several dependent variables and one or several independent variables. The research gives several implications to the suppliers policy. First, it is important for the supplers to manage customer's perception in order to maintain its reputation. Second, the size of suppliers becomes important because it can present good perception that the companies have positive value (honest, responsible, punctual, etc). Third, trustof the buyers is the key for building long-term relationship. Suggestion for next research is to add characler- isics of suppller's sales person to build full trustof the buyers, and to bring significant cultural role in creating tnrust.